Current and new challenges in occupational lung diseases. (15th November 2017) - De Matteis, Sara; Heederik, Dick; Burdorf, Alex; Colosio, Claudio; Cullinan, Paul; Henneberger, Paul K.; Olsson, Ann; Raynal, Anne; Rooijackers, Jos; Santonen, Tiina; Sastre, Joaquin; Schlünssen, Vivi; et al.
Occupational lung diseases are an important public health issue and are avoidable through preventive interventions in the workplace. Up-to-date knowledge about changes in exposure to occupational hazards as a result of technological and industrial developments is essential to the design and implementation of efficient and effective workplace preventive measures. New occupational agents with unknown respiratory health effects are constantly introduced to the market and require periodic health surveillance among exposed workers to detect early signs of adverse respiratory effects. In addition, the ageing workforce, many of whom have pre-existing respiratory conditions, poses new challenges in terms of the diagnosis and management of occupational lung diseases. Primary preventive interventions aimed to reduce exposure levels in the workplace remain pivotal for elimination of the occupational lung disease burden. To achieve this goal there is still a clear need for setting standard occupational exposure limits based on transparent evidence-based methodology, in particular for carcinogens and sensitising agents that expose large working populations to risk. The present overview, focused on the occupational lung disease burden in Europe, proposes directions for all parties involved in the prevention of occupational lung disease, from researchers and occupational and respiratory health professionals to workers and employers. Directions to face new challenges in occupational respiratory diseases due to changing industry and workforce http://ow.ly/Xnhb30fPgnV